Facile large-scale synthesis of three-dimensional graphene-like ordered microporous carbon via ethylene carbonization in CaX zeolite template. (July 2017) - Kim, Kyoungsoo; Kwon, Yonghyun; Lee, Taekyoung; Cho, Sung June; Ryoo, Ryong
Abstract: Recently, our laboratory has developed a zeolite-templated synthesis route to microporous three-dimensional (3D) graphene-like carbons via lanthanum-catalyzed carbonization of ethylene. In the present work, we optimized the ethylene carbonization conditions for a zeolite X template, using an inexpensive Ca 2+ -ion catalyst instead of La 3+ -ion catalyst. This synthesis gave a high carbon yield based on the template pore volume, and exhibited no significant amount of carbon deposition on the external surfaces. Single crystal X-ray diffraction analysis indicated that the carbon had 3D graphene- or nanotube-like frameworks along the surface of the zeolite pore walls, similar to the case of La 3+ catalyst. With a 70-g batch of carbon synthesis, we demonstrated the potential of this synthesis route for large-scale production that would bring about a wide range of practical applications. Graphical abstract: